POLA KEPEMIMPINAN KEPALA SEKOLAH DI LINGKUNGAN PONDOK PESANTREN - Huda, Imam Nur (Program Studi Manajemen Pendidikan, FKIP Universitas Palangka Raya, 2025)
This study aims to describe the leadership patterns of school principals at MA Futuhiyyah 2 Mranggen Demak, Central Java. This study uses a qualitative method with a descriptive type. The research sample consists of school principals at MA Futuhiyyah 2 Mranggen Demak, Central Java, selected using purposive sampling techniques. The data analysis used to interpret the findings employs the qualitative research data analysis method by Miles et al. (2014), which includes: data collection, data condensation, data presentation, and drawing conclusions. Data validation techniques use source triangulation and member checking. The research findings indicate that the leadership patterns of the principal of MA Futuhiyyah 2 Mranggen Demak consist of three patterns: democratic, communicative, and familial. Supporting factors for the principal's leadership include having a competent school management team and adequate school facilities. However, hindering factors include some teachers' lack of adaptability to the latest educational information and the need for space for entrepreneurship activities.